Elucidation of White Matter Tracts of the Human Amygdala by Detailed Comparison between High-Resolution Postmortem Magnetic Resonance Imaging and Histology - Mori, Susumu; Kageyama, Yusuke; Hou, Zhipeng; Aggarwal, Manisha; Patel, Jaymin; Brown, Timothy; Miller, Michael I.; Wu, Dan; Troncoso, Juan C. (Frontiers in Neuroanatomy, 2017)
The amygdala is one of the anatomical structures that has attracted intensive interest because of its potential involvement in various neuropsychiatric disorders. In recent years, attempts have been made to evaluate the integrity of the axonal connections from and to the amygdala under pathological conditions using MRI. Although the amygdalar pathways have been extensively studied in the past using animal models, the current anatomical references for the human brain are limited to histology-based resources at a small number of slice locations, orientations, and annotations. In this study, we performed high-resolution MRI (250 m) of postmortem samples, followed by serial histology sections. The histology data served as the ground truth to identify amygdalar pathways, and the anatomical delineation of the assigned structures was extended to 3D using the MRI data. We could clearly define the detailed anatomy of the stria terminalis and amygdalofugal pathway, as well as the anatomy of the nearby basal forebrain areas, including the substantia innominata. The results could help us to understand the detailed white matter structures associated with the amygdala and serve as an anatomical reference by which to design and interpret in vivo MRI data.